Institutional Quality and Poverty Reduction in ECOWAS Countries: Evidence from Driscoll and Kraay (Global Business Management Review (GBMR), 2023)
The rising situation of poverty especially in developing countries has been a disturbing issue to the academic environment and policymakers for a long time. Despite voluminous research on how various economic factors affect poverty reduction, the problem persists. Within this context, the current study evaluates the influence of institutional quality on poverty reduction among 12 countries of the Economic Community of West African States (ECOWAS) for the period of 1984-2018. The study employs the second-generation estimation techniques, specifically the Driscoll and Kraay (1998) estimation technique which is robust to cross-sectional dependence. The main findings indicate that improvement in the institutional quality arrangement will go a long way in reducing the poverty levels in the ECOWAS countries. Hence, the policy recommendation is all the countries within the sub-region need to put more efforts to strengthen the institutional environment in the sub-region.